Investigation of the Effect of Confining Pressure on the Mechanics-Permeability Behavior of Mudstone under Triaxial Compression - Lu Shi; Zhijiao Zeng; Zhiming Fang; Xiaochun Li (Geofluids)
Injecting CO2 into a reservoir disturbs the geostress field, which leads to variations in the permeability of caprock and affects its sealing performance. In this paper, the evolution characteristics of the permeability of Yingcheng mudstone were experimentally studied during deviatoric compression under different confining pressures. As the confining pressure increased, the strength of the mudstone increased bilinearly, the angle between the fault and the maximum principle stress increased, and the fault became flatter. During compression, the permeability of mudstone first decreased and then increased and the turning point of the permeability was between the onset of dilatancy and the turning point of volumetric strain; when the fault formed, the permeability increased sharply and the fault-induced increment was reduced exponentially with increasing confining pressure. In addition, the mudstone transformed to the ductile failure mode when the effective confining pressure was greater than 35 MPa, which means that the permeability did not jump within a small strain. Finally, a practical strain-based model of permeability evolution that separately considers compaction and dilatancy was proposed, and the predicted permeability values were in good agreement with the experimental results. This study revealed the effect of confining pressure on permeability evolution during compression and can help evaluate the sealing ability of mudstone caprock.